Effect of Cd2+ Molar Concentration in CdxZn(1−x)S Thin Film by Chemical Bath Deposition Technique Using Alternative Sulfur Precursor. (22nd February 2021) - Nurhafiza, K.; Chelvanathan, P.; Sobayel, K.; Munna, F. T.; Abdullah, Huda; Ibrahim, Mohd Adib; Techato, Kuaanan; Sopian, K.; Amin, N.; Akhtaruzzaman, Md.
Abstract : Ternary semiconductor Cdx Zn(1−x) S thin films are prepared by chemical bath deposition (CBD) using N-methyl thiourea as an alternative sulfur precursor. Molar concentration of CdSO4 has been varied from 0.01 M to 0.09 M during the fabrication process of Cdx Zn(1−x) S thin film. Effect of variation in Cd 2+ molar concentration on morphological, structural and opto-electrical properties of Cdx Zn(1−x) S thin film has been investigated. As grown films are found less crystalline and structural analysis suggests that Cdx Zn(1−x) S phase changes with the increase of Cd 2+ molar concentration. SEM images reveals that all the films exhibit granules-like morphology. Raman peak indicates that higher concentration of CdSO4 precursor forms more CdS in the Cdx Zn(1−x) S. Bandgaps of Cdx Zn(1−x) S thin films are found to be ranged from 2.44 eV to 2.95 eV for different Cd 2+ molar concentrations in the Cdx Zn(1−x) S thin films. Resistivity and carrier mobility of as grown Cdx Zn(1−x) S films ranged from 14.2 × 10 3 ohm-cm to 2.25 × 10 3 ohm-cm and 4.31 cm 2 (V s) −1 to 9.42 cm 2 (V s) −1, respectively. As all these findings affirms the credibility of using N-methyl thiourea as an alternative sulfur precursor for the development of Cdx Zn(1−x) S thin film by CBD process.